HPTLC fingerprint profile of antibacterial compound produced from forest soil Streptomyces SFA5 - Ponnuswamy, Shekar; Kannaiyan, Sathish Kumar; Venugopal, Gopikrishnan; Mannikkam, Radhakrishnan (Bangladesh Journal of Pharmacology, 2016)
The present study investigates the presence of antimicrobial compounds from potent isolate Streptomyces sp. SFA5 from the Sabarimala forest ecosystem, Western Ghats, Kerala, India. Preliminary screening revealed Streptomyces sp. SFA5 isolate shows significant inhibition against the bacterial and fungal pathogens. The antibacterial compound from isolate SFA5 was produced by submerged fermentation using yeast extract malt extract broth and extracted using different solvents. Among the different solvent extracts tested, the ethyl acetate extract of SFA5 shows maximum zone of inhibition against Staphylococcus aureus (23mm) and Bacillus cereus (24mm). A simple, sensitive and accurate HPTLC method has been performed for the quantitative estimation of bioactive compounds from ethyl acetate extract of Streptomyces sp. SFA5. The optimized solvent system for mobile phase in HPTLC Chromatogram is toluene: ethyl acetate: methanol: acetic acid (5:3:1:0.5, v/v/v/v). Results of HPTLC finger printing of ethyl acetate extract of the strain SFA5 at UV 254 and 366 with corresponding Rf values substantiate the presence of bioactive compounds. Video clip of Methodology: Production and extraction of bioactive compounds: 5 min 43 sec Click to watch